Early shunt complications in 46 children with hydrocephalus Complicações precoces de válvula de hidrocefalia em 46 crianças - Moisés Heleno Vieira Braga; Gervásio Teles C. de Carvalho; Rafael Augusto Castro Santiago Brandão; Franklin Bernardes Faraj de Lima; Bruno Silva Costa (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To determine the causes of early shunt complications in 46 children with hydrocephalus. METHOD: A retrospective study was conducted on 46 children submitted to ventriculoperitoneal shunt surgery between February 2005 and February 2007. RESULTS: Thirteen (28%) patients presented complications, which were due to infection in 9 (69%) and to malfunction of the shunt system in 4 (31%).The mean number of surgical procedures performed on patients who presented complications was 2.8 per patient, with a total of 46 surgeries in this group. All patients with infectious complications were identified during their hospital stay. CONCLUSIONS: Infection was the most common complication. The infection rate was proportional to the length of hospital stay. All patients with hydrocephalus due to tumors or myelomeningocele presented complications. A higher incidence of infections was observed in children older than 2 years. OBJETIVO: Determinar e as causas das complicações precoces nas válvulas de hidrocefalia de 46 crianças. MÉTODO: Um estudo retrospectivo foi realizado com 46 crianças submetidas a colocação de válvula de hidrocefalia no período de fevereiro de 2005 a fevereiro de 2007. RESULTADOS: Obtivemos 13 (28%) pacientes com complicações sendo 9 (69%) causadas por infecção e 4 (31%) por mal funcionamento da válvula de hidrocefalia. A média de procedimentos cirúrgicos realizados nos pacientes com complicações foi de 2,8 por paciente, sendo o total de 46 cirurgias neste grupo. Todos os pacientes com complicações infecciosas foram detectados durante a internação hospitalar. CONCLUSÕES: Infecção foi a complicação mais comum. O índice de infecção foi proporcional ao tempo de permanência hospitalar. Todos os pacientes portadores de hidrocefalia secundária a tumores ou mielomeningocele complicaram. As crianças maiores de 2 anos de idade tiveram maior incidência de infecções.